2002
DOI: 10.1073/pnas.072137099
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the biosynthesis of 2-carboxyarabinitol 1-phosphate through reduced expression of chloroplastic fructose 1,6-bisphosphate phosphatase and radiotracer studies with 14 CO 2

Abstract: 2-Carboxyarabinitol 1-phosphate limits photosynthetic CO2 assimilation at low light because it is a potent, naturally occurring inhibitor of ribulose 1,5-bisphosphate carboxylase͞oxygenase. Evidence is presented that this inhibitor is derived from chloroplastic fructose 1,6-bisphosphate. First, transgenic plants containing decreased amounts of chloroplastic fructose 1,6-bisphosphate phosphatase contained increased amounts of fructose 1,6-bisphosphate and 2-carboxyarabinitol 1-phosphate and greatly increased am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Decreases in the specific activity of RuBPCO previously observed under similar environmental conditions have been attributed to the presence in wheat and other plants of a day-time inhibitor(s) (Keys et al 1995, Parry et al 1997). An accumulation of precursor metabolites could increase the contents of the RuBPCO inhibitor (Andralojc et al 2002). We have previously found that EC increases, and ET decreases, the contents of metabolites, which also decrease as leaves age .…”
Section: Discussionmentioning
confidence: 94%
“…Decreases in the specific activity of RuBPCO previously observed under similar environmental conditions have been attributed to the presence in wheat and other plants of a day-time inhibitor(s) (Keys et al 1995, Parry et al 1997). An accumulation of precursor metabolites could increase the contents of the RuBPCO inhibitor (Andralojc et al 2002). We have previously found that EC increases, and ET decreases, the contents of metabolites, which also decrease as leaves age .…”
Section: Discussionmentioning
confidence: 94%
“…It has been speculated that the inhibitor may be formed non-enzymatically from RuBP in the chloroplast, given its favourable conditions for this process (Kane et al 1998). In this case, the levels of the inhibitor could increase in response to an accumulation of precursor metabolites, Plant Growth Regul (2011) 65:439-447 445 as reported for the nocturnal inhibitor of Rubisco, carboxyarabinitol 1-phosphate (Andralojc et al 2002). Consistent with this, we have found that elevated CO 2 increased the levels of carbohydrates and, possibly, of phosphorylated metabolites .…”
Section: Discussionmentioning
confidence: 93%
“…Using classic radio-tracer studies and the analysis of transgenic plants with decreased chloroplastic fructose 1,6-bisphosphate phosphatase expression, Andralojc et al (2002) confirm the biosynthetic pathway for CA1P from newly assimilated carbon. Sage (2002) provides an insightful review of the current understanding of Rubisco control over C 3 and C 4 photosynthesis at different temperature and CO 2 conditions and documents how Rubisco kinetic properties evolved to improve performance in the environment that the plants normally experience.…”
mentioning
confidence: 86%